Transcranial Magnetic Theta-Burst Stimulation of the Human Cerebellum Distinguishes Absolute, Duration-Based from Relative, Beat-Based Perception of Subsecond Time Intervals - Grube, Manon; Lee, Kwang-Hyuk; Griffiths, Timothy D.; Barker, Anthony T.; Woodruff, Peter W. (Frontiers in Psychology, 2010)
Cerebellar functions in two types of perceptual timing were assessed: the absolute (duration-based) timing of single intervals and the relative (beat-based) timing of rhythmic sequences. Continuous transcranial magnetic theta-burst stimulation (cTBS) was applied over the medial cerebellum and performance was measured adaptively before and after stimulation. A large and significant effect was found in the TBS (n = 12) compared to the SHAM (n = 12) group for single-interval timing but not for the detection of a regular beat or a deviation from it. The data support the existence of distinct perceptual timing mechanisms and an obligatory role of the cerebellum in absolute interval timing with a functional dissociation from relative timing of interval within rhythmic sequences based on a regular beat.